Percutaneous Lateral Pinning for Pediatric Supracondylar Fracture of Humerus - Acharya, Parimal; KC, Kapil Mani; Sigdel, Arun; Pangeni, Bandhu Ram; Marhatta, Suman (Nepal Orthopaedic Association Journal, 2016)
BACKGROUND: Pediatric supracondylar fractures of humerus are managed with closed reduction and percutaneous pin fixation. The cross pinning technique has advantage of stability over lateral pinning but puts the ulnar nerve in peril. The lateral pinning technique avoids iatrogenic nerve injury while providing comparable stability. In this study, we attempt to analyse the outcome and complications of lateral pinning. METHODS: We prospectively followed 33 children, with modified Gartland II band III supracondylar fractures of the humerus, after doing closed reduction and fixation with two to three percutaneous lateral pins. Any displacement of fracture after fixation was assessed with changes in anterior humeral line and serial measurement of Baumann's angle. The pins were removed after 3 weeks and the final outcome was assessed after three months and graded according to Flynn's criteria. RESULTS: We achieved excellent results in 17(51.51%) patients, good in 10(30.30%), fair in 4 (12.12%) and poor results in 2 (6.06%) patients. The mean age of the patients was 8.36 +/- 2.43 years with type III fractures (81.8%) being the commonest. 13 fractures were stabilized with two lateral pins and 20 fractures with 3 lateral pins. No loss of reduction was seen in fractures fixed with divergent pins. Two patients had cubitus varus deformity. There were no iatrogenic nerve injuries but cases which had been manipulated previously had greater elbow stiffness. CONCLUSION: Displaced supracondylar fractures can be fixed with divergent lateral pins after successful closed reduction with no risk of iatrogenic nerve injuries.